Bioreductively activatable prodrug conjugates of phenstatin designed to target tumor hypoxia. Issue 3 (1st February 2017) - Winn, Blake A.; Shi, Zhe; Carlson, Graham J.; Wang, Yifan; Nguyen, Benson L.; Kelly, Evan M.; Ross, R. David; Hamel, Ernest; Chaplin, David J.; Trawick, Mary L.; Pinney, Kevin G.
Graphical abstract: Abstract: A variety of solid tumor cancers contain significant regions of hypoxia, which provide unique challenges for targeting by potent anticancer agents. Bioreductively activatable prodrug conjugates (BAPCs) represent a promising strategy for therapeutic intervention. BAPCs are designed to be biologically inert until they come into contact with low oxygen tension, at which point reductase enzyme mediated cleavage releases the parent anticancer agent in a tumor-specific manner. Phenstatin is a potent inhibitor of tubulin polymerization, mimicking the chemical structure and biological activity of the natural product combretastatin A-4. Synthetic approaches have been established for nitrobenzyl, nitroimidazole, nitrofuranyl, and nitrothienyl prodrugs of phenstatin incorporating nor -methyl, mono -methyl, and gem -dimethyl variants of the attached nitro compounds. A series of BAPCs based on phenstatin have been prepared by chemical synthesis and evaluated against the tubulin-microtubule protein system. In a preliminary study using anaerobic conditions, the gem -dimethyl nitrothiophene and gem- dimethyl nitrofuran analogues were shown to undergo efficient enzymatic cleavage in the presence of NADPH cytochrome P450 oxidoreductase. Each of the eleven BAPCs evaluated in this study demonstrated significantly reduced inhibitory activity against tubulin in comparison to the parent anti-cancer agent phenstatin (IC50 = 1.0 μM). In fact, the majority of the BAPCs (seven of the eleven analogues) were not inhibitors of tubulin polymerization (IC50 > 20 μM), which represents an anticipated (and desirable) attribute for these prodrugs, since they are intended to be biologically inactive prior to enzyme-mediated cleavage to release phenstatin.